Digital reconstruction of the Puck 3 wreck hull - Litwinienko, Paweł (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The Puck 3 wreck is a 12th century clinker-built vessel, salvaged from the submerged remains of the medieval harbour in Puck, northern Poland, in 1990. Individual planks and other timbers were then passed on to the National Maritime Museum in Gdańsk for conservation. Following the procedures developed and used for the digital reconstruction of the other Puck harbour wreck, the longship P2, the timbers of the P3 cargo vessel were documented in 3D using the Faro Arm. This allowed for digital assembly of the individual timbers. On that basis a reconstruction of the complete hull was prepared and tested for hydrostatic properties.